Interaction of tantalum with gases - Pylypenko, M.M.; Drobyshevskaya, A.A. (Физическая инженерия поверхности, 2014)
Kinetics of tantalum degassing by vacuum extraction of gases of heated metal in temperature range 1675—2275 K is studied. Main component of the gases that separated from metal is nitrogen. The dependence for determination of the residual content of nitrogen in degassed tantalum is obtained. It was established that during heating in the temperature range 1825—1875 K tantalum maximally absorbs oxygen and nitrogen.